2023
DOI: 10.1161/jaha.122.028623
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Improves Myocardial Perfusion, Fibrosis, and Function in a Swine Model of Chronic Myocardial Ischemia

Abstract: Background Sodium‐glucose cotransporter‐2 inhibitors are cardioprotective independent of glucose control, as demonstrated in animal models of acute myocardial ischemia and clinical trials. The functional and molecular mechanisms of these benefits in the setting of chronic myocardial ischemia are poorly defined. The purpose of this study is to determine the effects of canagliflozin therapy on myocardial perfusion, fibrosis, and function in a large animal model of chronic myocardial ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…This study is a continuation of our previously published swine cohort that received a regular diet [ 19 ]. Sixteen 11-week-old Yorkshire swine (Cummings School of Veterinary Medicine of Tufts University Farm, North Grafton, MA, USA) arrived at our facility at 9 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is a continuation of our previously published swine cohort that received a regular diet [ 19 ]. Sixteen 11-week-old Yorkshire swine (Cummings School of Veterinary Medicine of Tufts University Farm, North Grafton, MA, USA) arrived at our facility at 9 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…To increase our knowledge of how SGLT-2 inhibition improves cardiac function, our lab chose to extensively study SGLT2 inhibitors in chronic myocardial ischemia using a swine model of chronic myocardial ischemia [ 19 ]. We previously demonstrated several remarkable changes with this model, including increased myocardial function, improved coronary perfusion, and decreased myocardial fibrosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Yorkshire swine (male and female; Tufts University, Medford, MA, USA), aged 8 to 10 weeks and weighing between 22 and 25 kg at the time of the initial procedure, were used. This pilot study was designed to assess technical feasibility using an established model of chronic myocardial ischemia developed by Dr. Sellke as previously described [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To induce chronic ischemia, a small left thoracotomy was performed, the pericardium was opened, and an ameroid constrictor composed of hygroscopic casein material cased in titanium (Research Instruments SW, Escondido, CA, USA) was sized and placed around the proximal left circumflex (LCX) coronary artery (Figure 2B).…”
Section: Animal Methodsmentioning
confidence: 99%
“…In experimental studies and clinical trials, it has been demonstrated that SGLT2is are cardioprotective independently from controlling glucose, for instance, canagliflozin attenuates fibrosis via reducing JAK/STAT signaling, activating adenosine monophosphate-activated protein kinase, and antioxidant signaling ( Sabe et al, 2023 ). In clinical practice, empagliflozin can significantly reduce mortality and hospitalization of HF patients ( Kang et al, 2020 ).…”
Section: Interventions For Cardiac Fibrosismentioning
confidence: 99%